2015
DOI: 10.1038/ncb3246
|View full text |Cite
|
Sign up to set email alerts
|

Competition for actin between two distinct F-actin networks defines a bistable switch for cell polarization

Abstract: Symmetry-breaking polarization enables functional plasticity of cells and tissues and is yet not well understood. Here we show that epithelial cells, hard-wired to maintain a static morphology and to preserve tissue organization, can spontaneously switch to a migratory polarized phenotype upon relaxation of the actomyosin cytoskeleton. We find that myosin-II engages actin in the formation of cortical actomyosin bundles and thus makes it unavailable for deployment in the process of dendritic growth normally dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
198
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(221 citation statements)
references
References 65 publications
16
198
2
Order By: Relevance
“…In this scheme, inhibition of formins or Arp2/3 shifts the turnover rate towards the Arp2/3-or formin-based kinetics, respectively (Burke et al, 2014;Fritzsche et al, 2013;Lomakin et al, 2015;Rotty et al, 2015;Suarez et al, 2015). To determine if such a balance was also at work in MCCs in vivo, we performed FRAP on apical actin after treatment with a specific Arp2/3 inhibitor, CK666.…”
Section: Rhoa Controls the Dynamics Of MCC Apical Emergencementioning
confidence: 99%
“…In this scheme, inhibition of formins or Arp2/3 shifts the turnover rate towards the Arp2/3-or formin-based kinetics, respectively (Burke et al, 2014;Fritzsche et al, 2013;Lomakin et al, 2015;Rotty et al, 2015;Suarez et al, 2015). To determine if such a balance was also at work in MCCs in vivo, we performed FRAP on apical actin after treatment with a specific Arp2/3 inhibitor, CK666.…”
Section: Rhoa Controls the Dynamics Of MCC Apical Emergencementioning
confidence: 99%
“…At the tissue level, this is manifested with the lack of the characteristic apical anisotropic constricted cell shape and invagination, thus revealing the importance of apico‐basal polarization of myosin‐II activity during morphogenesis of the ventral furrow. Similarly, subcellular polarization of myosin‐II is observed also during cell migration (front‐back; Yam et al , 2007) and cytokinesis (poles–cleavage furrow; Uehara et al , 2010), and a recent study has suggested a competitive mechanism for the accumulation of actomyosin in different parts of the cell (Lomakin et al , 2015). However, at the levels of optogenetic activation employed in this study (< 2‐fold up‐regulation of Rho signaling and myosin‐II levels), we did not observe a reduction in apical myosin‐II concentration.…”
Section: Discussionmentioning
confidence: 95%
“…Given all this information, interventions that impair CP function, such as CP knockdown or V-1 overexpression, would be predicted to reduce the formation of cortical actin structures built by the Arp2/3 complex (lamellipodia and pseudopodia) and promote the formation of cortical actin structures built by formins and VASP (filopodia). Of note, the increase in filopodia number seen upon CP knockdown/V-1 overexpression is probably also due in significant part to an increase in the amount of monomer available for formin/VASP after the reduction in Arp2/3-dependent nucleation (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Although both proteins are fairly effective at physically shielding the barbed end from CP (10,13,14), it is likely that their robustness as filopodia generators in vivo would be increased by a reduction in CP levels. Given the recent work demonstrating that formins and the Arp2/3 complex compete for G-actin in vivo (15)(16)(17), the increase in filopodia number seen upon CP knockdown may also be due in part to an increase in the amount of monomer available for formin/VASP after the reduction in Arp2/ 3-dependent nucleation caused by CP knockdown.The studies discussed above suggest that cells could regulate their "actin phenotype" by regulating their level of active CP. Consistent with CP regulation in vivo, estimates of the half-life of CP on the barbed end near the plasma membrane in living cells are approximately three orders of magnitude shorter than CP's half-life on the barbed in vitro (i.e., ∼2-15 s in cells vs. ∼30 min for pure proteins) (8, 18).…”
mentioning
confidence: 99%
See 1 more Smart Citation